Hubungan Dukungan Keluarga dengan Status Nutrisi pada Lansia - Nindya Erina Putri; Kartinah Kartinah (Journal of Telenursing (JOTING), 2023)
The study aims to determine the relationship between family support and nutritional status of the elderly in Ngadirejo Village. The type of research used in this research is quantitative research with a cross sectional approach. The results showed that elderly people with high family support who had good nutritional status were 38 respondents (41.3%), elderly people who had low family support with nutritional status were at risk of malnutrition as many as 1 respondent (1.1%), elderly people who had family support 7 respondents (7.6%) had low nutritional status with malnutrition, and most respondents had moderate family support who had nutritional status at risk of malnutrition as many as 46 respondents (50%). In conclusion, there is a relationship between family support and the nutritional status of the elderly in Ngadirejo Village. Keywords: Family Support, Elderly, Nutrition